Bhartiya Itihaas Ka Adhyayan Ek Parichay - Kosambi, Damodar Dharmanand (SAGE Publications, 2019)
The use of scientific methodology, modern techniques of interpretation, and selection and analysis of basic problems make An Introduction to the Study of Indian History a vivid and absorbing read. The author has thrown open new fields for research through this book, which serves as a critical guide to scientific historical thought. It helps the reader gain profound insight into the past by examining monuments, customs and surviving records. At the same time, the present is shown to be the inevitable result of a steady historical development. Complete grasp of the material and mastery of detail shown in the survey of the development from a pre-historic tribal society to the present machine-age make this volume a unique contribution to contemporary historiography. This book is the culmination of patient research and mature reflection of a profoundly original mind and has earned universal recognition and honour over the last few decades. Note: Now this ISBN-9788171540389 has a new identity.